If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3b + 10 = -35 Reorder the terms: 10 + -3b = -35 Solving 10 + -3b = -35 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -3b = -35 + -10 Combine like terms: 10 + -10 = 0 0 + -3b = -35 + -10 -3b = -35 + -10 Combine like terms: -35 + -10 = -45 -3b = -45 Divide each side by '-3'. b = 15 Simplifying b = 15
| D-1/2=10 | | X-(X-5)=16 | | (d+2)(d-5)=-6 | | cosh(x)=1.25 | | 1524x-12+22x=5541+1124x-41 | | 4x-2=9+5(x-3) | | 3q+17+14=19 | | 29=7+x+2+x | | 2x+1+3x+5+6x-31=180 | | (3xy+2yx)3= | | 12-3x=66x | | x/80=35/100 | | X+(X-5)=16 | | 5y-4=3y-18 | | 70=x+4 | | 3x^4-16x^2-81=0 | | g(x)=3f(x+1)-1 | | 28=4n+4-8 | | 4(5x-1)-(x+5)=24 | | 7x+145.5=6 | | f(x)=16x^4+8x^2+1 | | tan(19pi/12 | | 0=-2t(8t-75) | | -28=4n+4-8 | | 11x+1=5x+61 | | f(-4)=x^2-3x+9 | | 29=7+x+2 | | 2l+28=58 | | 5(n-4)=25 | | 6y=5(y+9) | | -5=y | | -8x+4(1+5x)=-6x-1 |